Isolating, cloning, and sequencing of the cry1C genes encoding protein crystal toxic to Lepidoptera - Van Tien Tran; Thi Hue Nguyen (Vietnam Journal of Science, Technology and Engineering)
Bacillus thuringiensis (Bt) is a gram-positive, spore-forming bacterium widely recognised for its ability to produce insecticidal crystal (Cry) proteins that are highly toxic to various insect orders. Among them, the cry1C gene encodes the Cry1C protein, which exhibits specific insecticidal activity against Lepidopteran larvae, a major group of agricultural pests responsible for significant crop losses worldwide. In this study, we aimed to isolate, clone, and sequence the cry1C gene from native Bt strains to support the development of environmentally friendly biological control agents. As concerns grow regarding the ecological and health impacts of synthetic chemical pesticides, Bt-based biopesticides have emerged as a sustainable alternative due to their host specificity and biodegradability. We utilised the polymerase chain reaction (PCR) technique with specific primers to identify Bt isolates harbouring the cry1C gene. A 288 bp fragment was successfully amplified from positive isolates and subsequently sequenced. Sequence analysis confirmed 100% homology with previously reported cry1C gene sequences in the GenBank database, verifying the presence and integrity of the target gene in selected Bt strains.